Chromium combination tannage of rural and minimal tanned crusts - Elhassan, Dr. Ardelshifa Mohammed (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Chrome tanning gives the tanned hide/ skins many good properties such as degree of fullness ,softness , resilience standard shrinkage temperature . The study aims to make use of this by a ppling combination tannage. This was done by treating the traditionally vegetable tanned leathers with semi chrome tanning . Vegetable tannin are a group of polyphenolic compounds extracted from plants and used tannage . The infusion and subsequent binding of vegetable tannins to animal hides or skins usually results in increased shrinkage temperature from the range 60-65c for an untanned hide skin to about 80c . The mechanism through which the vegetable tannins raise the shrinkage temperature of leather by the potential of forming multiple hydrogen bonds , it is considerable that they can cross link collagen molecules and there by stabilize the fibrillary network of the skin .Nevertheless , high shrinkage temperature is requiring by shoe upper manufactures to be 100c . Hence a combination tannage of chrome vegetable will improve the shrinkage temperature of the vegetable tannins and the feel of fullness of the chrome leather . Acacia nilotica tannins is used as retanning or pretanning agent for producing minimal crusts which are further semi chrome to give the properties of chrome vegetable combination tannage . Third sheep skins were minimally tanned and processed until finished leathers . The leather produced was analyzed for physical and chemical properties and showed good degree of fullness , softness and resilience . To encourage the rural tanner and promote their process and production third sheep skins which were tanned by rural process , stripped with soda ash and semi-chromed . The crusts were further processed up to finishing .The finished leather s were analyzed and showed good results . To help the rural tanners to increase their production and to cope with clean technology . A small experimental drum is designed and it can be easily put into service by the rural tanners with very low cost .